CONSERVATION OF PRINCIPLES OR OBJECTS? : An Approach of Conserving the Traditional Balinese Cultural Landscape in Urban Areas - Samadhi, Tjokorda Nirarta (DIMENSI (Journal of Architecture and Built Environment), 2004)
The idea of ’non-physical’ cultural heritage conservation and preservation has been around since the early 1980s, however such an idea was never specifically explored, particularly in regard of the Bali’s cultural heritage conservation and preservation. Based on pluralistic approach (Appleyard, 1976; Lynch, 1960; Rapoport, 1969, 1977), a research was conducted on 1998-1999 to gather some findings for the purpose of utilizing urban design as a means to produce Balinese towns conducive to cultural identity. This paper is developed from this research and it attempts to propose an approach of the conservation of the traditional Balinese cultural landscape in the urban areas. The approach relies on the understanding that a Balinese traditional townscape is deemed as cultural heritage, and consequently it develops within the urban design framework.